(untitled) (Research, Society and Development, 2022)
Scientific Dissemination (SD) is a method for disseminating scientific-academic knowledge whose objective is to democratize access to information and encourage the development of critical thinking, reaching different publics. Ludic-educational practices application as dissemination method is necessary for a more dynamic learning and greater cognitive development. Besides that, educational institutions are seen as important promoters of educational actions, especially in the health area. Knowing that adolescents are among the most vulnerable groups and have a basic knowledge deficiency about Sexually Transmitted Infections (STIs), the adoption of more effective interventions on the subject is crucial. Thus, with this work, the objective is to propose SD strategies in school spaces through playful-educational activities about IST as a pedagogical tool and health promoter. This proposal for Scientific Dissemination is composed of teaching strategies, different from the traditional expository model are highlighted, such as the promotion of knowledge through basic and preventive information about these infections and their impacts on health; interactive actions through quiz games entitled “Jogo de Tabuleiro Humano”, “Quiz Torta na Cara” and “Ida ao Posto de Saúde”; and dissemination of local Primary Health Care units. These ludic activities are relevant because they encourage the participation and teamwork of the students involved, in addition to favoring a more attractive and creative teaching-learning process, fundamental issues for the practice of health-promoting actions in the school environment.